2022
DOI: 10.1186/s12885-022-10102-8
|View full text |Cite
|
Sign up to set email alerts
|

Values of OAS gene family in the expression signature, immune cell infiltration and prognosis of human bladder cancer

Abstract: Background Bladder cancer (BLCA) is one of the most common genitourinary malignancies in the world, but its pathogenic genes have not been fully identified and the treatment outcomes are still unsatisfactory. Although the members of 2', 5'-oligoadenylate synthetase (OAS) gene family are known involved in some tumorous biological processes, the roles of the OAS gene family in BLCA are still undetermined. Methods By combining vast bioinformatic datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Apart from their antiviral activity, OAS proteins are also involved in cell growth, differentiation, and apoptosis ( Castelli et al, 1997; Huang et al, 2022; Salzberg et al, 1997 ). The genomic mutation and methylation of most OAS genes have been shown to alter their expression levels, which is associated with the levels of infiltrated CD4 + T cells and CD8 + T cells in the tumor microenvironment ( Gao et al, 2022 ). Secreted OAS2 has also been observed to inhibit CD3 zeta chain expression in T cells ( Dar et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their antiviral activity, OAS proteins are also involved in cell growth, differentiation, and apoptosis ( Castelli et al, 1997; Huang et al, 2022; Salzberg et al, 1997 ). The genomic mutation and methylation of most OAS genes have been shown to alter their expression levels, which is associated with the levels of infiltrated CD4 + T cells and CD8 + T cells in the tumor microenvironment ( Gao et al, 2022 ). Secreted OAS2 has also been observed to inhibit CD3 zeta chain expression in T cells ( Dar et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The level of OAS1 gene expression is closely linked to tumor onset and progression [ 68 ]. According to research, OAS1 is significantly downregulated in BLCA tissues, and this downregulation is linked to the clinical characteristics and prognosis of the tumor [ 69 , 70 ]. OAS1 enhances the immune cell’s capacity to fight viral infections by triggering the interferon signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, OASL is closely related to viral infection response and autoimmune diseases 13 . In addition, OASL plays a role in a variety of tumors, such as breast cancer, lung cancer, bladder cancer, and gastric cancer 14–17 . It has been reported that OASL is overexpressed in PDAC and is associated with poor outcomes in patients 18 .…”
Section: Introductionmentioning
confidence: 93%
“…13 In addition, OASL plays a role in a variety of tumors, such as breast cancer, lung cancer, bladder cancer, and gastric cancer. [14][15][16][17] It has been reported that OASL is overexpressed in PDAC and is associated with poor outcomes in patients. 18 Furthermore, we found that Pi16 can promote PDAC cell proliferation by regulating OASL, suggesting that the Pi16/OASL axis may be a promising new target for PDAC diagnosis and treatment.…”
mentioning
confidence: 99%